Gender and cultural differences in the use of facial emoji (مجلة ديالى للبحوث الانسانية, 2023)
Emojis are pictographs that are common in computer mediated communication and used in all platforms of the internet. An emoji obtains its meaning through its graphic resemblance to a physical object (smiling face). Emojis are used in a number of ways in daily life outside the computer mediated communication There are certain events used to indicate the importantance of emojis in communications. In 2015, The Oxford English Dictionary selected Face with Tears of Joy emoji as the word of the year.         The current study has adopted Danesy’s model in analyzing the meaning of emojis . It is concluded that emojis have less cultural variation than it is assumed to be and that is there are less cultural variations.